Effects of exercise on mortality rates of individuals with severe mental illness - Baron, David A.; Mishrekar, Asmita; Kazmi, Shan (Frontiers in Psychiatry, 2022)
Persons with severe mental illness have a 10-to-20-year shorter life span than the general public. Excess morbidity and mortality in this patient population has been described as a major public health challenge worldwide. Despite robust extant literature on the role of exercise in reducing morbidity and mortality, especially from cardiovascular disease and diabetes (highly prevalent in this patient population), Very few clinical programs or clinical research projects currently exist to implement and study the effects of exercise on decreasing morbidity and mortality in this highly vulnerable patient population. Given the global lack of trained mental health providers, the need to integrate healthcare providers from different disciplines, such as nurses, physical therapists, occupational therapists, physician assistants, cannot be overstated. This mini-review will provide an historic perspective and current data supporting the need to establish exercise, and other Lifestyle Psychiatry interventions, as a key component of treatment for all patients with serious mental illness.